Coaching of English Class: Meningkatkan Kemampuan Kosa Kata Berbahasa Inggris Siswa Menggunakan Media Smart TV: Coaching of English Class: Improving Students' English Vocabulary Skills Using Smart TV Media - Syam, Andi Akbar; Gunawan, Gunawan; Tahir, Dewi Sartika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service program aims to increase students' motivation, focus, and proficiency in English. This service program emphasizes writing and speaking skills, especially mastery of basic sentence-level English vocabulary through Smart TV media. Students prepare teaching and learning activities and offer teaching in the form of material. Students are prepared to receive relevant and meaningful training activities to develop motivation and English language skills through the use of interesting and communicative audio-visual teaching media. The PKM results aim to strengthen students' ability to master English vocabulary on the topic or material being taught, considering the importance of English for students at MTs Sinoa. In addition, this service program allows students to improve their English through more modern media and attractive visuals.